Bentuk Masalah Sosial Tokoh Perempuan Dalam Novel The House On Mango Street Karya Sandra Cisneros - Nathasya Nur Aprilla (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2022)
The House On Mango Street is a novel by Mexican-American author Sandra Cisneros published in 1984 about a girl who has experienced all the joy, fear, challenge, and exciting transformation into a teenager in hispanic environment in america. The purpose of this study is to clarify what social problems the female characters in Sandra Cisneros's novel The House on Mango Street are experiencing. The method used in this study is a descriptive qualitative method using a literary and sociological approach. The subject of this research is the social issue of Sandra Cisneros's novel The House on Mango Street. The subject of this study is the novel "House on Mango Street" by Sandra Cisneros. The data in this study are words, expressions, and dialogues between characters that show problems encountered in the story.